Aflatoxin contamination of groundnut (Arachis hypogaea L.): Predisposing factors and management interventions. (April 2019) - Asare Bediako, Kwabena; Ofori, Kwadwo; Offei, Samuel Kwame; Dzidzienyo, Daniel; Asibuo, James Yaw; Adu Amoah, Richard
Abstract: Groundnut ( Arachis hypogaea L.) is one of the most important oilseed crops in world agricultural trade. It is considered an important crop by virtue of its contribution to satisfying the protein needs of many households who cannot afford animal protein. Production and consumption of groundnuts are hampered among others, by Aspergillus flavus and Aspergillus parasiticus infection which subsequently contaminate groundnuts with aflatoxins. Aflatoxins are associated with acute and chronic toxicities in humans and animals causing induction of tumor, liver damage, liver cirrhosis, and carcinogenic, estrogenic, teratogenic, and immunosuppressive effects. Contaminated food crops expose millions of people to high risk of chronic aflatoxin exposure. Aflatoxin contamination can occur in the field before harvest, and after harvest during curing, storage and transportation. The major factors influencing A. flavus and A. parasiticus infection in groundnuts before harvest are insect damage to the developing seed/pod, drought and high soil temperatures. After harvest, environmental conditions such as high humidity and high temperatures promote fungal infection and aflatoxin accumulation. Agronomic practices such as crop rotation, use of resistant varieties, insect control, timely planting and harvesting, weed control, adequate fertilization and late season irrigation can reduce pre-harvest aflatoxin production. Additionally, atoxigenic fungi can be applied in the field to competitively displace toxigenic fungi to reduce the population of toxigenic fungi in the soil. Post-harvest aflatoxin contamination of groundnuts can be minimized by rapid and proper drying following harvesting, proper transportation and packaging, sorting and post-harvest insect control. Sourcing information from different research and review articles, and book chapters, this paper provides extensive review on the predisposing factors and management of groundnut aflatoxin contamination before and after harvest. Highlights: Aspergillus flavus and A. parasiticus infect and produce aflatoxins in groundnuts. Drought, high temperatures and high humidity promote pre- and post-harvest infection. Plant breeding, agronomic practices and biocontrol could reduce pre-harvest infection. Sorting and total drying before storage could provide post-harvest infection control.